Modulation of circulating protein biomarkers following TRC105 (anti‐endoglin antibody) treatment in patients with advanced cancer. (14th February 2014) - Liu, Yingmiao; Starr, Mark D.; Brady, John C.; Dellinger, Andrew; Pang, Herbert; Adams, Bonne; Theuer, Charles P.; Lee, Nam Y.; Hurwitz, Herbert I.; Nixon, Andrew B.
Abstract TRC105 is an endoglin‐targeting drug that possesses anti‐angiogenic and antitumor potential. Analysis of the initial phase I trial of TRC105 demonstrated good tolerability and efficacy in cancer patients. In this report, we analyzed multiple circulating biomarkers at baseline, cycle 2 day 1 (C2D1), and end of study (EOS) for each patient. The baseline level and the fold change from baseline to both C2D1 and EOS for each marker were statistically analyzed. At C2D1, seven markers were significantly downregulated (angiopoietin‐2 [Ang‐2], insulin‐like growth factor‐binding protein‐3 [IGFBP‐3], plasminogen activator inhibitor‐1 [PAI‐1] total, platelet‐derived growth factor [PDGF]‐AA, PDGF‐BB, thrombospondin‐1 [TSP‐1], and vascular endothelial growth factor [VEGF]‐D). Meanwhile, seven markers were upregulated by C2D1 (E‐Cadherin, soluble Endoglin [sEnd], E‐Selectin, interleukin‐6 [IL‐6], osteopontin [OPN], TSP‐2, and von Willebrand factor [vWF]). At EOS, seven markers were upregulated including Ang‐2, C‐reactive protein (CRP), intercellular adhesion molecule‐1 (ICAM‐1), IGFBP‐1, IL‐6, TSP‐2, and vascular cell adhesion molecule‐1 (VCAM‐1). A statistical trend was also seen for increases of VEGF‐A and placenta growth factor (PlGF) at EOS. Throughout treatment, sEnd levels significantly increased, an observation that was recapitulated in cultured endothelial cells. This is the first report of plasma‐based biomarkers in patients receiving TRC105. TRC105 treatment by C2D1 was associated with decreases in several angiogenic factors, including Ang‐2, PDGF isoforms, and VEGF isoforms, offering insight into the mechanisms underlying TRC105's anti‐angiogenic, antitumor function. Increases in sEnd were the most significant of all observed biomarker changes and may reflect direct drug effects. Additionally, biomarker changes in response to TRC105 are distinct from those seen in patients treated with VEGF‐targeting drugs, suggesting the possible utility of combining these two classes of angiogenesis inhibitors in patients.